Correlation Between Crystallization Behavior and Mechanical Properties of Biodegradable Poly(Caprolactone-co-Cyclohexene Carbonate). Issue 15 (13th October 2018) - Lin, Limiao; Xu, Yonghang; Qin, Jiaxian; Wang, Shuanjin; Xiao, Min; Meng, Yuezhong
ABSTRACT: The isothermal and nonisothermal crystallization behaviors of poly( ε -caprolactone) and poly(caprolactone- co -cyclohexene carbonate) were investigated utilizing differential scanning calorimeter and polarized optical microscope. The kinetic of isothermal crystallization could be well defined by Avrami equation, while Mo model was successful to describe the nonisothermal crystallization. Based on the obtained kinetic parameters, poly(cyclohexene carbonate) segments not only act as a nucleating agent accelerating nucleating rate but also restrict the transport of poly( ε -caprolactone) segments decelerating growth rate. The mechanical properties of polymers were investigated using DMA and nanoindentation. It shows that the insertion of hard poly(cyclohexene carbonate) segments improves Young's modulus and heat resistance but reduces hardness of copolymers. GRAPHICAL ABSTRACT: